The impact of the reforms of the 2000s and the Arab Spring of 2011 on the performance of the Egyptian banking sector - Ahmed L. M. Ahmed (Journal of Banking and Financial Economics)
This paper aims to assess the current condition of the Egyptian banking sector, based on the past reforms of the 2000s. This analysis is based on data from the Central Bank of Egypt (CBE), data from the Egyptian banking sector and the literature review. The main finding is that despite many changes in the political and economic scene that drove the country into a crisis, the Egyptian banking sector was able to work well in the post-2008 period, achieving high growth rates. This study contributes to the academic literature on factors influencing financial development in emerging counties, based on the analysis of the Egyptian banking.